Hadith #2847 - Sunan Abi Dawud - Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Byan bin Bashr al-Ahmsi بيان بن بشر الأحمسي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan Abi Dawud)
I asked the Prophet (ﷺ) ,and said: I set off my trained dogs, and they catch (something) for me: may I eat (it)? He said: When you set off trained dogs and mention Allah’s name, eat what they catch for you. I said: Even if they killed (the game)? He said: Even if they killed (the game) as long as another dog does not join it. I said: I shoot with a featherless arrow, and it strikes the target, may I eat (it) ? He said: If you shoot with a featherless arrow and mention Allah’s name, and it
Grade: Sahih

Hadith #3650 - Sunan Abi Dawud - Abdullah ibn al-Zubayr; Amir bin 'Abdullah عامر بن عبد الله بن الزبير بن العوام; Amr bin 'Awn/'Auf bin Aws; Byan bin Bashr al-Ahmsi بيان بن بشر الأحمسي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
I asked Abu `Amr: What are they writing? He said: The sermon which he heard that day.
Grade: Sahih